Periode Masa Jabatan Hakim Konstitusi dan Implikasinya terhadap Kemandirian Kekuasaan Kehakiman (Term of Office for Constitutional Justices and Its Implications against Judicial Independence) - Novianto Murti Hantoro (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2020)
Constitutional justices have a five-year term and can be re-elected for only one subsequent term. There has been an effort to correct this provision through a request for judicial review of the Constitutional Court Law. Still, there is no decision by the Constitutional Court which states that the term of office of constitutional justice is against the 1945 Constitution of the Republic of Indonesia. This paper analyzes the need to reform the provisions regarding the term of office of constitutional justices associated with the principle of judicial independence. An analysis of the term of office of constitutional justices was also carried out by comparing international principles and practices in other countries. The term of office of 5 years and can be re-elected has its weaknesses, because it opens up opportunities for political influence and controversy in candidacy proposal for the second term of constitutional justices. This term of office needs to be changed with a longer time length without extension combined with the retirement age. The determination of the term of office of constitutional justices which is related to the judicial independence cannot be separated from the requirements, selection, supervision, and dismissal of constitutional justices. Those requirements, mechanisms for selection, supervision, and dismissal of constitutional justices also need to be improved. AbstrakHakim konstitusi memiliki periode masa jabatan lima tahun dan dapat dipilih kembali hanya untuk satu kali masa jabatan berikutnya. Ketentuan ini telah coba dikoreksi melalui permohonan uji materi terhadap UU Mahkamah Konstitusi (MK), tetapi tidak ada putusan MK yang menyatakan periode masa jabatan hakim konstitusi bertentangan dengan UUD NRI Tahun 1945. Tulisan ini menganalisis mengenai perlunya reformulasi ketentuan mengenai periode masa jabatan hakim konstitusi dikaitkan dengan prinsip kemandirian kekuasaan kehakiman. Analisis mengenai periode masa jabatan hakim konstitusi juga dilakukan dengan membandingkan prinsip internasional dan praktik di negara lain. Periode masa jabatan 5 tahun dan dapat dipilih kembali memiliki kelemahan, karena membuka peluang pengaruh politik dan kontroversi pada pengajuan calon hakim konstitusi periode kedua. Periode masa jabatan ini perlu diubah dengan masa jabatan yang lebih lama tanpa perpanjangan dikombinasikan dengan usia pensiun. Penentuan periode masa jabatan hakim konstitusi yang dikaitkan dengan kemandirian kekuasaan kehakiman tidak dapat lepas dari persyaratan, seleksi, pengawasan, dan pemberhentian hakim konstitusi. Persyaratan, mekanisme seleksi, pengawasan, dan pemberhentian hakim konstitusi juga perlu disempurnakan.